CARE: A Collision-Aware Mobile Robot Navigation in Grid Environment using Improved Breadth First Search. (September 2021) - Tripathy, Hrudaya Kumar; Mishra, Sushruta; Thakkar, Hiren Kumar; Rai, Deepak
Abstract: In recent years, there is an increasing interest in designing autonomous vehicles such as Mobile Robots. However, one of the fundamental needs of Mobile Robots is a collision-free navigation with an optimal path from the source to the destination. In this paper, a collision-free low-complexity Mobile Robot navigation scheme called Collision Aware Mobile Robot navigation in Grid-Environment is designed. The proposed scheme uses the Radio Frequency based Identification method for Mobile Robot localization, the hybrid approach for the path planning, and a predefined decision table for the navigation. The algorithms are implemented in two stages, construction of virtual world and generation of optimal shortest path. The algorithms' performance is analyzed in grid-based environment of size 5 × 5, 20 × 20, 35 × 35, and 50 × 50 with four different cases. It is observed that for the environment with no obstacles, the robot explores fewer cells in finding the shortest path. However, the number of turning in the shortest path is always less in the environment with some obstacles than in the case of whole virtual world exploration. The performance results show the effectiveness of the proposed scheme for Mobile Robot navigation in the grid environment. Highlights: Grid-based virtual environment created for Mobile Robot navigation in free space. Radio Frequency Identification method is employed for Mobile Robot localization. An Improved Breadth First Search with Greedy strategy is designed for path planning. The CARE reduces cyclomatic complexity by reducing the number of repetition of nodes.